2022
DOI: 10.21203/rs.3.rs-1433034/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inheritance of Resistance to Race 5 of Powdery Mildew fungus Podosphaera xanthii in Melon and development of Race 5-Specific High Resolution Melting Markers

Abstract: Powdery mildew (PM), caused by the biotrophic fungus Podosphaera xanthii, drastically reduces the yield and quality of melon (Cucumis melo L.). Knowledge on the genetic control and high throughput molecular markers linked with resistance against this disease are essential for breeding programs. The bioassay study of the F1 and F2 populations derived from the parents, ‘PMR 5’ (♂) and ‘SCNU1154’ (♀) revealed a monogenic dominant nature of resistance to the devastating race, race 5. Besides, we developed three SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nevertheless, the phenotyping and genotyping of the advanced backcrossed lines allowed us to narrow the resistance interval to a region of approximately 400 kb between HRM markers Oidio3 (chr12: 21,870,304 bp) and Oidio2 (chr12: 22,251,703 bp) ( Table 3 ). This narrowed region is not located within the previously proposed resistance QTL and is also outside the boundaries proposed for other resistance sources such as Edisto27, MR-1, PMR5, WM6, PI 124112, and PI 134198 [ 17 , 19 , 24 , 25 , 26 , 30 , 35 , 36 , 63 ] ( Figure 1 ). Nevertheless, the recessive gene present in TGR-1551 is unique, since no recessive genes conferring resistance to more than one Px race have been reported previously in melons, and this resistance could be conferred by a gene different from those derived from other accessions.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Nevertheless, the phenotyping and genotyping of the advanced backcrossed lines allowed us to narrow the resistance interval to a region of approximately 400 kb between HRM markers Oidio3 (chr12: 21,870,304 bp) and Oidio2 (chr12: 22,251,703 bp) ( Table 3 ). This narrowed region is not located within the previously proposed resistance QTL and is also outside the boundaries proposed for other resistance sources such as Edisto27, MR-1, PMR5, WM6, PI 124112, and PI 134198 [ 17 , 19 , 24 , 25 , 26 , 30 , 35 , 36 , 63 ] ( Figure 1 ). Nevertheless, the recessive gene present in TGR-1551 is unique, since no recessive genes conferring resistance to more than one Px race have been reported previously in melons, and this resistance could be conferred by a gene different from those derived from other accessions.…”
Section: Discussionmentioning
confidence: 69%
“…This QTL from Fukino et al [ 17 ] was strongly linked to the microsatellite markers associated with the QTL derived from TGR-1551 (TJ29, CMBR111, and CMBR150) [ 33 ]. This candidate interval proposed by Fukino et al [ 17 ] has recently been confirmed by Hong et al [ 35 ] and the resistance of MR-1 to race 1 has recently been mapped to the same region [ 19 , 24 ]. More recently, Howlader et al [ 36 ] described three SNP markers associated with specific resistance to race 5 of Px in chromosome 12, in close proximity to the microsatellite markers previously described by Fukino et al [ 17 ] and Beraldo-Hoischen et al [ 33 ].…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations